The Influence of Principal Leadership Style and Work Motivation on Teacher Performance: Evidence from Public Elementary Schools in Indonesia - Irra Julia Saputri; Alhadi Yan Putra; Nurlina Nurlina (Journal of Social Work and Science Education, 2026)
This study aims to analyze the influence of principal leadership style and teachers’ work motivation on the performance of elementary school teachers in Talang Kelapa District, Banyuasin Regency. Employing a quantitative approach with a survey design, the study involved 109 teachers from public elementary schools selected as research respondents. Data were collected using structured questionnaires that measured principal leadership style, teachers’ work motivation, and teacher performance. The collected data were then analyzed using simple and multiple linear regression techniques to examine both partial and simultaneous effects among the variables. The results of the t-test indicate that principal leadership style has a positive and significant effect on teacher performance (t = 4.420; Sig. = 0.000), contributing 15.4% to the variance in teacher performance. Similarly, teachers’ work motivation shows a positive and significant effect on teacher performance (t = 5.796; Sig. = 0.000), with a contribution of 23.9%. Furthermore, the results of the simultaneous test reveal that principal leadership style and teachers’ work motivation jointly have a significant effect on teacher performance (F = 19.693; Sig. = 0.000), with a coefficient of determination (R²) of 0.271. These findings confirm that teacher performance is influenced by both organizational and individual factors. Strengthening principal leadership practices and enhancing teachers’ work motivation are therefore essential strategies for improving teacher performance and supporting the effectiveness of elementary education.